Análisis bibliográfico sobre cómo las redes 5g afectan la privacidad de los datos y las posibles estrategias para protegerlos. - Vera García, Juan Ubaldo (2025)
The review explores how 5G networks impact data privacy and proposes strategies to mitigate risks. 5G networks increase exposure to vulnerabilities due to massive interconnection, virtualization of functions, and decentralization of their infrastructure. These features facilitate data interception, unauthorized tracking, and attacks on IoT devices. At a technical level, measures such as end-to-end encryption, network segmentation, and multifactor authentication stand out. However, implementation faces economic and technical barriers. At the regulatory level, regulations such as the GDPR lead the way in data protection, but the absence of global standards limits their effectiveness in emerging markets. Recommendations include strengthening international regulatory frameworks, fostering collaboration between sectors, educating users, and investing in advanced technologies. This balanced approach between technology and regulation is essential to maximize the benefits of 5G without compromising privacy.